New experimental results of combined SO2 and NO removal from simulated gas stream by NaClO as low-cost absorbent - Mondal M.K.; Chelluboyana V.R. (My University, 2025)
The experiments were performed in a magnetic stirrer reactor to study the simultaneous absorption of NO and SO2 using NaClO solution from simulated gas stream. The effects of various operating parameters viz., absorbent concentration, reaction temperature, initial SO2 and NO concentration and initial pH of NaClO solution on simultaneous removal of SO2 and NO were investigated in regard to coal-fired thermal power plant stack gases. The maximum removal efficiencies of SO2 and NO were observed as 100% and 92%, respectively at 313K, initial NaClO solution pH 5.8 and 0.01M NaClO concentration. The important rate governing steps with appropriate reaction mechanisms for simultaneous removal of SO2 and NO using NaClO as absorbent were also discussed. © 2012 Elsevier B.V.